Categories That Should Be Removed From Mental Disorders Classifications: Perspectives and Rationales of Clinicians From Eight Countries. Issue 3 (22nd December 2014) - Robles, Rebeca; Fresán, Ana; Medina‐Mora, María Elena; Sharan, Pratap; Roberts, Michael C.; de Jesus Mari, Jair; Matsumoto, Chihiro; Maruta, Toshimasa; Gureje, Oye; Ayuso‐Mateos, José Luís; Xiao, Zeping; Reed, Geoffrey M.
<x xml:space="preserve">Abstract</x> Objective To explore the rationales of mental health professionals (mainly psychiatrists and psychologists) from 8 countries for removing specific diagnostic categories from mental disorders classification systems. Method As part of a larger study, 505 participants indicated which of 60 major disorders should be omitted from mental disorders classification systems and provided rationales. Rationale statements were analyzed using inductive content analysis. Results The majority of clinicians (60.4%) indicated that 1 or more disorders should be removed. The most common rationales were (a) problematic boundaries between normal and psychopathological conditions (45.9% of total removal recommendations), (b) problematic boundaries among mental disorders (25.4%), and (c) problematic boundaries between mental and physical disorders (24.0%). The categories most frequently recommended for deletion were gender identity disorder, sexual dysfunction, and paraphilias, usually because clinicians viewed these categories as being based on stigmatization of a way of being and behaving. A range of neurocognitive disorders were described as better conceptualized as nonpsychiatric medical conditions. Results were analyzed by country and country income level. Although gender identity disorder was the category most frequently recommended for removal overall, clinicians from Spain, India, and Mexico were most likely to do so and clinicians from Nigeria and Japan least likely, probably because of social and systemic factors that vary by country. Systematic differences in removal rationales by country income level may be related to the development, structure, and functioning of health systems. Conclusion Implications for development and dissemination of the classification of mental and behavioral disorders in WHO's ICD‐11 are discussed.